Limiting the caesarean section rate in low risk pregnancies is key to lowering the trend of increased abdominal deliveries: an observational study - Delbaere Ilse; Cammu Hendrik; Martens Evelyne; Tency Inge; Martens Guy; Temmerman Marleen (BMC, 2012)
Abstract Background As the rate of Caesarean sections (CS) continues to rise in Western countries, it is important to analyze the reasons for this trend and to unravel the underlying motives to perform CS. This research aims to assess the incidence and trend of CS in a population-based birth register in order to identify patient groups with an increasing risk for CS. Methods Data from the Flemish birth register 'Study Centre for Perinatal Epidemiology' (SPE) were used for this historic control comparison. Caesarean sections (CS) from the year 2000 (N = 10540) were compared with those from the year 2008 (N = 14016). By means of the Robson classification, births by Caesarean section were ordered in 10 groups according to mother - and delivery characteristics. Results Over a period of eight years, the CS rise is most prominent in women with previous sections and in nulliparous women with a term cephalic in spontaneous labor. The proportion of inductions of labor decreases in favor of elective CS, while the ongoing inductions of labor more often end in non-elective CS. Conclusions In order to turn back the current CS trend, we should focus on low-risk primiparae. Avoiding unnecessary abdominal deliveries in this group will also have a long-term effect, in that the number of repeat CS will be reduced in the future. For the purpose of self-evaluation, peer discussion on the necessity of CS, as well as accurate registration of the main indication for CS are recommended.